‘What Fools these Mortals Be’ : What Do Mortals Play At when They Play with Fiction? - Casal, Teresa (2017)
'Lord, what fools these mortals be' is Puck's pronouncement on Shakespeare's lovers in A Midsummer Night's Dream (III.2.115). Yet, the invisible Puck is himself the creature of a mortal's imagination and features in a play performed by mortals who are repeatedly faced with mirror images of the enterprise they are engaged in. These imaginative exchanges between humans and non-humans raise the question addressed in this paper: what to mortals play with when they create non-human creatures through whose estranged eyes they view humans' predicament? Following Puck's lead, this chapter focuses on three works that overtly play with fiction and provide insights into why and how we resort to fiction: Shakespeare's play A Midsummer Night's Dream, Wim Wenders's film Wings of Desire (1987), and Jennifer Johnston's novel Two Moons (1998).